2014
DOI: 10.2967/jnumed.113.126615
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Imaging Characteristics and Microregional Distribution of 4 Hypoxia PET Tracers

Abstract: We compared the imaging characteristics and hypoxia selectivity of 4 hypoxia PET radiotracers (18F-fluoromisonidazole [18F-FMISO], 18F-flortanidazole [18F-HX4], 18F-fluoroazomycin arabinoside [18F-FAZA], and 64Cu-diacetyl-bis(N4-methylsemicarbazone) [64Cu-ATSM]) in a single murine xenograft tumor model condition using small-animal PET imaging and combined ex vivo autoradiography and fluorescence immunohistochemistry. Methods Nude mice bearing SQ20b xenograft tumors were administered 1 of 4 hypoxia PET tracers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 32 publications
6
76
1
3
Order By: Relevance
“…Sharing the same mechanism of accumulation into hypoxic cells, FAZA and pimonidazole, a commonly used hypoxia marker in histochemical studies, have been reported to show similar intratumoral distributions (11,16). This observation has been confirmed in the present study (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Sharing the same mechanism of accumulation into hypoxic cells, FAZA and pimonidazole, a commonly used hypoxia marker in histochemical studies, have been reported to show similar intratumoral distributions (11,16). This observation has been confirmed in the present study (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…However, several recent studies have noted differential intratumoral distributions of Cu-ATSM and nitroimidazole compounds and raised questions on whether Cu-ATSM accumulation is truly hypoxia-dependent (10,11). In the present study, we detected a very limited overlap between areas of high accumulation of FAZA and Cu-ATSM in xenografts derived from human cancer cell lines of different origins and several CTOSs in which intratumoral distribution of PET tracers is similar to that observed in clinical studies (24).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…64 Cu-ATSM has a high tumor-to-background ratio and has shown promising results in small clinical studies, in which the tumor-to-muscle ratio was able to predict treatment outcome (11)(12)(13). However, the robustness of 64 Cu-ATSM as a marker of hypoxia has been questioned, because preclinical studies have reported temporal changes in tumor uptake and cell-type-specific differences in hypoxia selectivity (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Table 1 provides an overview of major studies using 64 Cu-ATSM in small-animal tumor xenograft models.…”
mentioning
confidence: 99%
“…Whole-tumor montage images were obtained by acquiring multiple fields at 40· magnification, followed by alignment using MicroSuite Biologic Suite (version 2.7; Olympus). IHC and autoradiographic images were registered using Adobe Photoshop (CS6) as previously described (28).…”
Section: Autoradiography and Histologymentioning
confidence: 99%